2020
DOI: 10.1088/2053-1591/abce84
|View full text |Cite
|
Sign up to set email alerts
|

Bioinert coatings of Ti-Ta-N for medical implants obtained by electric explosion spraying and subsequent electron-ion-plasma modification

Abstract: The purpose of the research was to form a Ti-Ta-N- system bioinert coating on Ti6Al4V alloy surface as well as to study its structure and properties. The main contribution of the research is in the following. Electro-explosion spraying of tantalum coating on VT6 titanium alloy surface was pioneered in the research. After that the processing of the coating by low-energy high-current electron beam and subsequent nitriding was carried out in a single technological cycle. It has been established that a nanocrystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…According to the authors of [20], the COF values are significantly lower in the case of Ti-10Ta than the pure Ti material, as well as Ti-5Ta, which confirms the statement that a larger amount of the alloying element corresponds to a lower friction coefficient. The authors of [40] have studied the coefficient of friction Ti-Ta-N coatings deposited on VT6 alloy for medical implants, and the results showed that it is about 0.3. Furthermore, it was found that the COF of the Ti-Ta-N coating is lower than that of the base VT6 alloy.…”
Section: R Peer Review 6 Of 13mentioning
confidence: 99%
“…According to the authors of [20], the COF values are significantly lower in the case of Ti-10Ta than the pure Ti material, as well as Ti-5Ta, which confirms the statement that a larger amount of the alloying element corresponds to a lower friction coefficient. The authors of [40] have studied the coefficient of friction Ti-Ta-N coatings deposited on VT6 alloy for medical implants, and the results showed that it is about 0.3. Furthermore, it was found that the COF of the Ti-Ta-N coating is lower than that of the base VT6 alloy.…”
Section: R Peer Review 6 Of 13mentioning
confidence: 99%